The Mental Health Continuum–Short Form (MHC–SF) in the Argentinean Context: Confirmatory Factor Analysis and Measurement Invariance - María Laura Lupano Perugini; Guadalupe de la Iglesia; Alejandro Castro Solano; Corey Lee M. Keyes (Europe's Journal of Psychology, 2017)
The present research aimed at studying the psychometric properties of the Mental Health Continuum–Short Form (MHC–SF; Keyes, 2005) in a sample of 1,300 Argentinean adults (50% males; 50% females). Their mean age was 40.28 years old (SD = 13.59). The MHC–SF is a 14 item test that assesses three components (i.e., emotional, social, and psychological) of well-being. Convergent and divergent evidence of construct validity was assessed by conducting confirmatory factor analysis, cross-validation, factorial invariance, and correlations with external criteria. Internal consistency was studied using Cronbach’s alphas. Results indicated an adequate fit of a three-dimensional model. This structure was also confirmed, and was invariant throughout sex and age. The emotional well-being scores converged with life satisfaction and positive affect measures; the psychological well-being scale had a positive association with the presence of meaning in life; and the social well-being scores showed a positive and strong correlation with an external measure of well-being. Also, all scores were negatively associated with negative affect, search of meaning in life, and presence of depression symptoms. Internal consistency was .89 for the MHC–SF. Furthermore, the findings supported the two - continua model of mental health.